Dioxazolones as electrophilic amide sources in copper-catalyzed and -mediated transformations - Lee, Seungmin; Kim, Minsuk; Han, Hyewon; Son, Jongwoo (Beilstein Journal of Organic Chemistry, 2025)
Over the past decade, dioxazolones have been widely used as N-acylamide sources in amidation processes of challenging substrates, typically employing precious transition metals. However, these catalytic systems often present several challenges associated with cost, toxicity, stability, and recyclability. Among the 3d transition metals, copper catalysts have been gaining increasing attention owing to their abundance, cost-effectiveness, and sustainability. Recently, these catalytic systems have been applied to the chemical transformation of dioxazolones, conferring a convenient protocol towards amidated products. This review highlights recent advancements in the synthetic transformations of dioxazolones, with particular examples of copper salts.
Keywords: amidation; copper salts; dioxazolones; electrophilic nitrogen; N-acyl nitrene